Adopting renewable energies to meet the carbon reduction target: Is forest carbon sequestration cheaper?. (1st May 2022) - Liu, Wan-Yu; Chiang, Yi-Hua; Lin, Chun-Cheng
Abstract: In most countries, the current goal for greenhouse gas emission reduction is to achieve a 50% reduction by 2050 with a carbon neutrality target. Most energy policies have been to adopt at least 20% renewable energies in the country energy portfolio. This study conducted a comparative cost analysis on various carbon emission reduction options: reducing fossil energies (including coal, natural gas, and petroleum), increasing renewable energies (including hydroelectric power, wind power, photovoltaics, and wood fuel), and increasing afforestation (including coniferous forests, broadleaved forests, and mixed coniferous-broadleaved forests). In analyzing the discounted costs per unit of carbon reduction, this study explored the costs of these options at a fixed amount of carbon reduction, which means the lower the costs, the more effective the carbon emission reduction. Taking Taiwan as an example, the results indicated that coal-fired power has the lowest cost (US$24.80 per ton of CO2 ). The costs of other energy sources (i.e., natural gas, petroleum, hydroelectric power, wind power, solar power, and wood fuel) are US$79.72–182.17 per ton of CO2 . The cost of afforestation for reducing carbon emissions is US$34.68–64.82 per ton of CO2, lower than the cost of adopting renewable energies assuming no technological advancement in current renewable energies. Highlights: Emission reduction options include reducing fossil energies, increasing renewable energies, and increasing afforestation. A comparative cost analysis was conducted on the above options to achieve the carbon reduction target. The lower the costs, the more effective the emission reduction. Producing forest carbon sequestration indeed costs lower than other options.